2011
DOI: 10.1124/jpet.111.186833
|View full text |Cite
|
Sign up to set email alerts
|

Salsolinol Stimulates Dopamine Neurons in Slices of Posterior Ventral Tegmental Area Indirectly by Activating μ-Opioid Receptors

Abstract: Previous studies in vivo have shown that salsolinol, the condensation product of acetaldehyde and dopamine, has properties that may contribute to alcohol abuse. Although opioid receptors, especially the -opioid receptors (MORs), may be involved, the cellular mechanisms mediating the effects of salsolinol have not been fully explored. In the current study, we used whole-cell patch-clamp recordings to examine the effects of salsolinol on dopamine neurons of the ventral tegmental area (VTA) in acute brain slices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 43 publications
10
56
0
Order By: Relevance
“…These findings are also in line with evidence showing that SAL effects are blocked by μ-opioid receptor antagonists; e.g., conditioned place preference (Matsuzawa et al, 2000); in vitro dopaminergic neurons activation (Xie et al, 2012); dopamine release in the nucleus accumbens (Hipólito et al, 2011); locomotor activation (Hipólito et al, 2010) and increased ethanol consumption (Quintanilla et al, 2014). An alternative mechanism by which SAL could activate opioid transmission is by increasing the release of endogenous opioids, such as β-endorphins.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These findings are also in line with evidence showing that SAL effects are blocked by μ-opioid receptor antagonists; e.g., conditioned place preference (Matsuzawa et al, 2000); in vitro dopaminergic neurons activation (Xie et al, 2012); dopamine release in the nucleus accumbens (Hipólito et al, 2011); locomotor activation (Hipólito et al, 2010) and increased ethanol consumption (Quintanilla et al, 2014). An alternative mechanism by which SAL could activate opioid transmission is by increasing the release of endogenous opioids, such as β-endorphins.…”
Section: Discussionsupporting
confidence: 85%
“…Recent electrophysiological studies in slices of posterior VTA have shown that incubation with SAL (10 −8 M to 10 −6 M) results in an increased firing of dopamine neurons. These stimulatory effects of SAL on dopaminergic neurons are abolished by the addition of naltrexone (Xie et al, 2012). As proposed by Xie et al (2013), SAL can indirectly activate dopaminergic neurons in the VTA through the inhibition of local GABAergic interneurons controlling the activity of dopaminergic neurons, playing a key role on the rewarding responses to SAL exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings coupled with data from in vitro studies showing that ACD stimulates VTA DA neuronal activity at concentrations 1200–2000 fold lower than that required for EtOH suggest that ACD is critical component required for EtOH stimulated DA activity within the VTA (Brodie and Appel, 1998; Brodie et al, 1999; Diana et al, 2008). A recent paper has reported that SAL is also capable of stimulating VTA DA neuronal activity at concentrations 10-1,000 fold lower than the lowest effective concentration of ACD (Xie et al, 2012a). …”
Section: The Neurobiological Actions Of Etoh and Etoh Metabolites Witmentioning
confidence: 99%
“…However, the full transgression from MOR activity to increased DA neuronal activity within the pVTA, and subsequent increase in DA release downstream, is indeed complex. Xie and colleagues have reported that SAL stimulates DA neurons within the pVTA indirectly by activating MORs which in turn inhibit of gama-amino butyric acid (GABA) neurons (Xie et al, 2012a) while also increasing glutamatergic signaling into the pVTA (Xie and Ye, 2012b). Overall, it is likely that the rewarding/reinforcing properties of both ACD and SAL in the pVTA are dependent on DA release within the AcbSh and the DA activity is modulated via MORs.…”
Section: The Neurobiological Actions Of Etoh and Etoh Metabolites Witmentioning
confidence: 99%